Flatness based Control of Single Phase Grid Connected Photovoltaic System Associated with a Shunt Active Power Filter. Issue 12 (2022) - Hekss, Z.; Abouloifa, A.; Echalih, S.; Lachkar, I.; Aroudi, A. El; Giri, F.
Abstract: The present paper proposes a new controller design method based on the flatness approach of single-phase full bridge shunt active power filter (SAPF) connected to photovoltaic system. The main control objective is threefold: (i) extracting the maximum active power in the output photovoltaic panel using an appropriate maximum power point tracking (MPPT) algorithm; (ii) regulation of the voltage of the DC link capacitor with the MPPT requirement to ensure the power exchanged between PV source and AC power grid; (iii) compensation for undesired harmonic and reactive currents caused by the non-linearity of electronic power loads, i.e. power factor correction (PFC). In this paper, the problem is dealt with designing a new two-loop cascaded controller in which the inner loop is constructed using a flatness approach to ensure the unity power factor. The outer loop consists mainly of filtered proportional-integral (PI) regulator, that assures a tight regulation of the voltage across the photovoltaic panel with an incremental conductance (IC) algorithm to meet MPPT requirement. The theoretical model and its controller are validated by numerical simulation within the MATLAB/SimPowerSystems environment.